Perbandingan Kompetensi Profesional Guru Berdasarkan Perbedaan Latar Belakang Pendidikan Mata Pelajaran Sejarah Indonesia Di MAN 2 Mandailing Natal Tahun Ajaran 2020/2021 - indah sari; Zafri Zafri (Jurnal Kronologi, 2021)
The purpose of this study was to identify significant differences in the professional competence of teachers based on the educational background of Indonesian history subjects at MAN 2 Mandailing Natal for the 2020/2021 school year. This study of research used is ex post facto. Ex post facto in Latin means ex post facto, which is a study where the independent variables have occurred when the researcher started by observing the dependent variables in a study. The technique used to compare the professional competence of teachers based on different educational backgrounds of teachers in the Indonesian history subject at MAN 2 Mandailing Natal for the 2020/2021 academic year is through descriptive analysis and test requirements in the form of normality test, homogeneity test, and hypothesis testing. Based on the results of research conducted at MAN 2 Mandailing Natal, there is a difference between the professional competence of teachers with historical education backgrounds and the professional competences of non-historical teachers in history subjects at MAN 2 Mandailing Natal in the academic year 2020/2021. This is evidenced by the average value of the professional competence ability of teachers with historical education background has an average of 127.22 and the professional competence of non-historical teachers has an average of 86.54. This is also evident from the percentage of students who state that the professional competence of teachers with historical education background is very good, namely reaching 85,1%, while the percentage of students who say that the professional competence of the teacher is very good for teachers who do not have a historical education background is only 16,2%.